2005
DOI: 10.1210/jc.2005-0089
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Adrenal Hyperplasia Due to 11-Hydroxylase Deficiency: Functional Characterization of Two Novel Point Mutations and a Three-Base Pair Deletion in theCYP11B1Gene

Abstract: Congenital adrenal hyperplasia is a group of autosomal recessive disorders second most often caused by deficiency of steroid 11-hydroxylase (CYP11B1) due to mutations in the CYP11B1 gene. We studied the functional and structural consequences of two novel missense mutations (W116C, L299P) and an in-frame 3-bp deletion (DeltaF438) in the CYP11B gene, detected in three unrelated families. All patients are suffering from classical CYP11B1 deficiency. In vitro expression studies in COS-7 cells revealed a decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 48 publications
1
40
0
4
Order By: Relevance
“…We found that 41 compound heterozygotes or homozygotes for select missense or nonsense mutations-namely P49L, R141Q, W260X, G267S, L299P, T318M, T318R, A331V, Q356X, A368D, R374Q, V441G, G444D, G446V, and R448H-present with moderate to severe classic CAH because of 11β-hydroxylase, confirming prior results (3,(14)(15)(16)(17)(22)(23)(24). These patients were mainly from Croatia, Tunisia, Africa, Turkey, and Saudi Arabia.…”
Section: Discussionsupporting
confidence: 88%
“…We found that 41 compound heterozygotes or homozygotes for select missense or nonsense mutations-namely P49L, R141Q, W260X, G267S, L299P, T318M, T318R, A331V, Q356X, A368D, R374Q, V441G, G444D, G446V, and R448H-present with moderate to severe classic CAH because of 11β-hydroxylase, confirming prior results (3,(14)(15)(16)(17)(22)(23)(24). These patients were mainly from Croatia, Tunisia, Africa, Turkey, and Saudi Arabia.…”
Section: Discussionsupporting
confidence: 88%
“…8 The mutagenesis was performed using the QuikChange XL Site-Directed Mutagenesis Kit according to the manufacturer's protocol (Stratagene, Amsterdam, The Netherlands). The introduction of the mutations was confirmed by sequencing the complete cDNA.…”
Section: Site-directed Mutagenesismentioning
confidence: 99%
“…Western blot analysis using a rabbit antihuman CYP11B1 antibody (kindly provided by Dr H Takemori, Department of Molecular Physiological Chemistry, Osaka University Medical School, Osaka, Japan) was performed on the basis of a standard protocol to ensure the expression and translation of CYP11B1 wild-type and mutant proteins. 8 …”
Section: Western Blotmentioning
confidence: 99%
See 2 more Smart Citations